Storage-Dependent Effects of Oregano Essential Oil on Lipid Peroxidation and Total Antioxidant Capacity in the Grapeseed Oil - Opryshko, Maryna; Tkachenko, Halina; Kurhaluk, Natalia; Buyun, Lyudmyla; Maryniuk, Myroslava; Gyrenko, Oleksandr (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2021)
Natural preservatives such as essential oils can be used as alternatives to chemical additives which could extend the shelf life of various food products. The knowledge about them can have important economic responsiveness by a decrease of spoilage-induced losses. The purpose of the current study was to investigate the content of 2-thiobarbituric acid reactive substances (TBARS) and total antioxidant capacity (TAC) in the grapeseed oil with the use of a commercial oregano essential oil (Etja, Elblag, Poland) as an antioxidant agent by monitoring the lipid peroxidation and antioxidant capacity. The effect of the oregano essential oil on the oxidative stability of the grapeseed oil was evaluated throughout 120 days of storage. The current results demonstrated that administration of oregano essential oil, exhibiting free radical scavenging activity determined by TBARS assay, exerts beneficial effects on preventing lipid peroxidation in grapeseed oil by limiting the TBARS levels and simultaneously increase of total antioxidant capacity, especially at 15–60 days of storage. At 60–120-day periods of storage, the TBARS levels were significantly lowered from control samples. The highest level of total antioxidant capacity was observed on 30-days compared to the control samples. Thus, edible adding containing essential oils have potential application in the plant oils to maintain their characteristics during the different shelf life.